2020
DOI: 10.3389/fped.2020.00175
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention: No Associations of Strength and Cardiorespiratory Fitness Status With Arterial Stiffness in Young School Children

Abstract: Pulse wave velocity (PWV) and central systolic blood pressure (CSBP) are well-established biomarkers of arterial stiffness. Further, fitness is known to be an important protective factor in adults in respect of vascular stiffening. However, the association of both muscular and cardiorespiratory fitness (CRF) with arterial properties in younger individuals has been inconsistent. The aim of the present study was to investigate the relationship between anthropometric data, CRF, strength status, and arterial stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Relative grip strength is determined by comparing absolute grip strength to BMI, primarily to account for the influence of body size on grip strength. However, the correlation between absolute grip strength and arterial stiffness is inconsistent [6][7][8][9]. A study conducted in an elderly population living in a Japanese community found that there was an independent correlation between grip strength and arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative grip strength is determined by comparing absolute grip strength to BMI, primarily to account for the influence of body size on grip strength. However, the correlation between absolute grip strength and arterial stiffness is inconsistent [6][7][8][9]. A study conducted in an elderly population living in a Japanese community found that there was an independent correlation between grip strength and arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of socio-demographic characteristics and healthrelated factors were considered as covariates in the analysis, with reference to related published studies [6][7][8][9]. The sociodemographic factors considered were age, sex, educational level, and marital status.…”
Section: Potential Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of socio-demographic characteristics and health-related factors were considered as covariates in the analysis, with reference to related published studies [6][7][8][9]. The sociodemographic factors considered were age, sex, educational level, and marital status.…”
Section: Potential Covariatesmentioning
confidence: 99%
“…Muscle strength, which is considered by the latest guidelines as a core indicator of sarcopenia [2,5], also deserves attention because of its association with arterial stiffness and because it is more readily available and applicable for risk screening, disease prediction, and management. Muscle strength is often assessed in clinical settings using grip strength, although Recent research has been inconclusive when it comes to the link between grip strength and arterial stiffness [6][7][8][9]. Irrespective of gender, there is a positive correlation between grip strength and Body Mass Index (BMI) in middle-aged and older populations [10].…”
Section: Introductionmentioning
confidence: 99%